Effect of pit space differences of sauce-flavor Baijiu production on the quality of the fourth-round base liquor - LIAO Fengmei, CHEN Renyuan, YANG Xueli, ZHAO Cheng, LI Xiaobo, YU Fangqiang, WANG Ye, ZHANG Hanren, WU Xinying (Zhongguo niangzao, 2025)
In order to investigate the quality differences of base liquor produced from fermented grains in different spatial locations of sauce-flavor (Jiangxiangxing) Baijiu pit, the volatile components in the base liquor of the fourth-round sauce-flavor Baijiu were quantitatively analyzed using gas chromatography-flame ionization detection (GC-FID), and the differences in volatile flavor components of the base liquor produced from different spatial positions of the fermented grains were analyzed by principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA). The contribution of different compounds to the aroma characteristics of the base liquor was evaluated by combining the aroma activity value (OAV). The PCA results showed that the three types of base liquors produced from the fermented grains of surface, middle, and bottom pit were well distinguished. 12 differential compounds were screened by OPLS-DA combined with variable importance projection (VIP) values, including ethyl caproate, n-propanol, and ethyl acetate. Combining the aroma activity value (OAV>1, VIP>1), it was found that ethyl caproate and ethyl butyrate contribute greatly to the flavor of base liquor produced from the fermented grains of bottom pit. The correlation analysis between differential compounds and aroma characteristics showed that acetic acid, octanoic acid, and ethyl acetate were significantly and extremely significantly positively correlated with floral and fruity aromas (P<0.05, P<0.01), while they were significantly or extremely significantly negatively correlated with cellar aroma and sauce aroma (P<0.05, P<0.01); Furfural, butyric acid, hexanoic acid, etc. were significantly positively correlated with Quxiang (P<0.01), while they were significantly negatively correlated with Liangxiang (P<0.01). This study provided a basis for understanding the aroma difference of base liquor produced by fermented grains at different locations in the pits, and laid a foundation for exploring the fermentation mechanism of sauce-flavor Baijiu pits.